Association of neutrophil-to-lymphocyte ratio and risk of all-cause and cardiovascular mortality in adults with metabolic dysfunction-associated steatotic liver disease: a population-based cohort study - Zhang, Ying; Zhang, Ai-Hua; Li, Rong-Li; Li, Wen-Jun; Liu, Yun; Li, Teng (Frontiers in Medicine, 2024)
Background and objective: Inflammation is key to metabolic dysfunction-associated steatotic liver disease (MASLD) development. Nevertheless, the correlation between the inflammatory marker, neutrophil-to-lymphocyte ratio (NLR), and the MASLD prognosis remains unclear. We aim to determine the link between NLR and mortality risk in MASLD.The MASLD adult participants from the 1999-2018 National Health and Nutrition Examination Survey (NHANES) database were evaluated. Utilizing restricted cubic spline (RCS) analyses, as well as Cox proportional hazards (PH) models, the associations between NLR and all-cause mortality (ACM) and cardiovascular mortality (CVM) were analyzed in MASLD. Subgroup analyses and interaction tests were conducted to validate these associations. Moreover, we used sensitivity analyses to ascertain the robustness of the results.Results: Through 115 months of median follow-up, 2,307 of the 16,859 participants with MASLD died, including 650 deaths from cardiovascular causes. RCS analyses showed positive linear associations between NLR and both ACM and CVM. In the multivariable-adjusted Cox PH model, a one-unit elevation in NLR was related to a hazard ratio (HR) of 1.16 (95% confidence interval [CI]: 1.12-1.21) for ACM and 1.21 (95% CI: 1.15-1.27) for CVM. Participants were classified into higher (≥ 2.88) and lower (< 2.88) NLR groups employing the maximally selected rank statistics. The higher NLR group had a significantly elevated ACM (HR 1.38,) and CVM (HR 1.64, 95% CI:1.32-2.03) risk compared to the lower NLR group. The associations were consistent in subgroup analyses based on age, gender, BMI, hypertension, and diabetes, with no significant interaction between NLR and these characteristics. Sensitivity analyses affirmed the main outcome's robustness.A raised NLR independently predicts escalated ACM and CVM in MASLD.